The Implementation of Blindfold Game to Improve Students' Vocabulary Mastery - Harpia; Mujahidah; Ahdar (Institut Agama Islam Negeri Parepare, 2020)
In studying English, the first component that has to learn is vocabulary. Someone who wants to master 4 language skills, he has to master a few words even everything. When learning listening, needs vocabulary, reading needs vocabulary, especially when learning to write, all needs vocabulary. That is the reason why the students have to master the vocabulary in learning English. This research was aimed to see the improvement of vocabulary mastery of students before and after learning process through blindfold game. The results of the research are useful for the teacher and students. The teacher should aware that it is important to supplied before teaching make the students more active in learning process. The researcher was conducted at MTs DDI Lil Banat Parepare, the sample of this research were the students of VIII.C class which is consisted 19 students. This research was used pre-test and post-test data. The result of this research showed that there was improving of students’ vocabulary mastery. Based on the analysis, the researcher found that Blindfold game is able to improve the vocabulary mastery. The students’ vocabulary mastery was improved significantly by mean score of the pre-test was 46.05 and the mean score of posttests was 78.57, they showed that the mean score in post-test was better that the mean score in pre-test. Thus, alternative hypothesis ( ) stating that Blindfold game could improve the students’ vocabulary mastery and could make the classroom be active.